Using integrated weed management systems to manage herbicide-resistant weeds in the Canadian Prairies - Tidemann, Breanne Darlene; Harker, K. Neil; Shirtliffe, Steve; Willenborg, Christian; Johnson, Eric; Gulden, Robert; Lupwayi, Newton Z.; Turkington, T. Kelly; Stephens, Emma C.; Blackshaw, Robert E.; Geddes, Charles M.; Kubota, Hiroshi; et al. (Frontiers in Agronomy, 2023)
While herbicides have been a dominant and effective weed control strategy for decades in western Canada, herbicide resistance and the lack of new modes of action have resulted in weed management challenges. Integrated weed management strategies, have been shown to be successful in controlling certain weed species that are problematic in cropping systems. The objective of this study was to investigate integrated weed management strategies that have been successful on individual species to determine their applicability to a multiple weed species that may coexist in a field. In addition, harvest weed seed control was incorporated into these integrated weed management strategies to determine its impact western Canadian cropping systems. A five-year rotational study was conducted from 2016-2020 at Beaverlodge, Lacombe, and Lethbridge, AB, Scott, and Saskatoon, SK, and Carman MB that incorporated integrated weed management strategies such as rotational crop diversity (including winter annuals and perennials), increased seeding rates, crop silaging, chaff collection, with or without in-crop herbicides. This research confirmed success in managing some species of weeds such as wild oat when increased seeding rates, two years of early cut silage barley, and competitive winter cereals were incorporated into a cropping system, even when no in-crop herbicides were applied. However, some weed growth morphologies (e.g., twining weeds) or life cycles (e.g., facultative winter annuals) were not managed successfully with this combination of strategies. Chaff collection provided incremental weed control benefits but did not serve as a replacement for herbicidal weed control. Weed densities had an apparent impact on the success of these integrated weed management strategies, suggesting the sooner they are adopted the more likely they are to be successful at maintaining or reducing weed densities. This study showed the ability to reduce reliance on herbicides with strategies that can be effective in western Canada, but also highlighted the need for further understanding of different weed species and their responses to integrated weed management strategies, as well as the complexity of managing a weed community with integrated weed management.